Prognosis of Morbid Obesity Patients With Advanced Heart Failure. Issue 4 (1st August 2013) - Nagarajan, Vijaiganesh; Cauthen, Clay A.; Starling, Randall C.; Tang, Wai Hong Wilson
Abstract : Obese patients have been noted to have better prognosis in many conditions including heart failure. We hypothesize that this favorable prognosis for obesity may not be seen in patients with morbid obesity and advanced heart failure. A total of 501 consecutive patients with advanced heart failure referred for heart transplant evaluation to the Cleveland Clinic were studied. Patients were categorized into 3 groups based on their body mass index score as nonobese (≤30 kg/m 2 ), obese (30.1–40 kg/m 2 ), and morbidly obese (≥40 kg/m 2 ). There were fewer cardiovascular risk factors in the morbidly obese group. Unadjusted event‐free survival rates were 48.4%, 57.4%, and 28.6% in the nonobese, obese, and morbidly obese groups, respectively ( P =.02). In univariate analysis, both the nonobese group (hazard ratio [HR], 1.44; 95% confidence interval [CI], 1.09–1.91; P =.01) and the morbidly obese group (HR, 2.46; 95% CI, 1.40–4.30; P =.002) had significantly higher risk of all‐cause mortality/transplantation compared with the obese group. This difference persisted in multivariate analysis after adjustment for confounding factors. Our study re‐emphasizes the presence of an obesity paradox even in patients with very advanced heart failure. This favorable prognosis, however, may not be relevant in patients with morbidly obesity. Cardiovascular risk factors may not contribute to this phenomenon